ANALISIS PEMAHAMAN AKUNTANSI PADA PELAKU USAHA KULINER DI SEKITAR LHOKSUKON - Irnianita Irnianita; Ghazali Syamni; Neo Agustina (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
The purpose of this study was to analyze the understanding of accounting in the culinary business operators around Lhoksukon. Object research is around Lhoksukon, south Lhoksukon Gampong Mns. Pante, Mns. Asan, East Lhoksukon Sampoiniet, west Lhoksukon, KM 4, Matangkuli, Northern Lhoksukon Kede Lhoksukon, Landeng, Tanah Luas. The Data Collection Techniques used is Questionnaire. Descriptive Qualitative Data Analysis Methods. Research shows that businesses around Lhoksukon culinary already understand and implement accounting systems in business. Only a small number of businesses that do not understand and implement accounting systems in business. This illustrates that the culinary business operators have very limited knowledge of accounting.